Recombination correlates with synaptonemal complex length and chromatin loop size in bovids-insights into mammalian meiotic chromosomal organization - Ruiz-Herrera, Aurora; Vozdova, Miluse; Fernández, Jonathan; Sebestova, Hana; Capilla, Laia; Frohlich, Jan; Vara, Covadonga; Hernández-Marsal, Adrià; Sipek, Jaroslav; Robinson, Terence J; Rubes, Jiri (Chromosoma, 2017)
Homologous chromosomes exchange genetic information through recombination during meiosis, a process that increases genetic diversity, and is fundamental to sexual reproduction. In an attempt to shed light on the dynamics of mammalian recombination and its implications for genome organization, we have studied the recombination characteristics of 112 individuals belonging to 28 different species in the family Bovidae. In particular, we analyzed the distribution of RAD51 and MLH1 foci during the meiotic prophase I that serve, respectively, as proxies for double-strand breaks (DSBs) which form in early stages of meiosis and for crossovers. In addition, synaptonemal complex length and meiotic DNA loop size were estimated to explore how genome organization determines DSBs and crossover patterns. We show that although the number of meiotic DSBs per cell and recombination rates observed vary between individuals of the same species, these are correlated with diploid number as well as with synaptonemal complex and DNA loop sizes. Our results illustrate that genome packaging, DSB frequencies, and crossover rates tend to be correlated, while meiotic chromosomal axis length and DNA loop size are inversely correlated in mammals. Moreover, axis length, DSB frequency, and crossover frequencies all covary, suggesting that these correlations are established in the early stages of meiosis.
Keywords: MutL homolog 1; Rad51 Recombinase; rekombinace genetická; dvouřetězcové zlomy DNA; rekombinasa Rad51; meióza; myši; Chromosomes, Mammalian; přežvýkavci; Mice; savčí chromozomy; Recombination, Genetic; mužské pohlaví; Synaptonemal Complex; DNA Breaks, Double-Stranded; zvířata; Meiosis; Ruminants; Animals; MutL Protein Homolog 1; Male; synaptonemální komplex